DESIGNING A SMALL CORPORATE BUILDING WITH FOUR WORKING COMPUTER DEPARTMENTS USING DISTANCE VECTOR ROUTING PROTOCOL - RIP: DESIGNING A SMALL CORPORATE BUILDING WITH FOUR WORKING COMPUTER DEPARTMENTS USING DISTANCE VECTOR ROUTING PROTOCOL - RIP - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a small corporate building with four working computer departments using dynamic routing protocol - RIP is designed and made. Dynamic routes are the most important step in the construction of any computer network. Subnetting is one of the best network tools with that each system and network administrator is able to divide one specific computer network into many subnetworks. Thereby, some network administrators, security professionals and network architects can use the free of charge software program Cisco Packet Tracer in order to design and administer different corporate computer networks.